2020
DOI: 10.1111/eje.12556
|View full text |Cite
|
Sign up to set email alerts
|

Final year dental students' career plans, work patterns, work‐life balance and domestic life in New Zealand and Australia

Abstract: Dental health care plays an essential role in maintaining the wellbeing of New Zealanders and Australians and is considered an important healthcare resource in New Zealand and Australia. With the dental healthcare environment and demands in treatment changing, as well as challenges posed by an ageing population, it is pertinent to gain an insight into new graduates' career aspirations and the factors influencing their decisions in order to maintain and further develop this resource. In 2009, the number of regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This study confirms previous findings that gaining experience is vitally important for new dentists when they take their first steps in their careers. 18 , 19 , 20 New dentists seem to find it easy to start out in the profession. The difficulties they encounter regard the responsibility of making clinical choices and the work pace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study confirms previous findings that gaining experience is vitally important for new dentists when they take their first steps in their careers. 18 , 19 , 20 New dentists seem to find it easy to start out in the profession. The difficulties they encounter regard the responsibility of making clinical choices and the work pace.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, undergraduates indicate that gaining experience is an important factor in their choices for the first years of their careers. 18 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all students made at least some reference to their professional identity and how this is still in the process of forming. Therefore, we concluded that social support aids careerrelated decision-making and professional identity commitment, and support provided in the form of a more experienced colleague as a mentor or a close supervisor would certainly help recent graduates, as several studies have expressed (Stringer and Kerpelman, 2010;Hakkarainen and Mikkola, 2019;Keinänen et al, 2020;Mei et al, 2020). A constructive way of action at work is also linked to the way in which newly graduated dentists feel secure to gather experiences, ask for help and grow professionally.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, it has been found that new graduates need social support and supportive communication to build their professional identities, especially when they are entering working life ( Hakkarainen and Mikkola, 2019 ). Graduating dental students have considered mentorship to be one of the most important factors in job selection after graduating ( Stringer and Kerpelman, 2010 ; Li et al , 2018 ; Mei et al , 2020 ). The transition to working life is a major step for any newly graduated dentist ( Hakkarainen and Mikkola, 2019 ), causing stress and uncertainty in both professional and private life ( Di Pierro, 2010 ).…”
Section: Introductionmentioning
confidence: 99%